Optimizing Hydroponic Production through Liquid Organic Fertilizer, Solar Cells, and Digital Financial Management in Gajahan Village - Rakhma, Luluk Ria; Eni Setyowati; Muchlison Anis (Universitas Muhammadiyah Surakarta, 2025)
The Gajah Tani Makmur Women Farmers Group (KWT) in Gajahan Village has 62 members with 500 m² of land used for hydroponic cultivation. Partners face a number of obstacles, namely (1) less than optimal production due to expensive nutrients, (2) limited electricity resources for hydroponic irrigation, (3) not yet using modern financial bookkeeping, and (4) no experience in utilizing digital marketing. To address these problems, community service activities were carried out in several stages, namely stage 1 socialization in the form of an introduction to solar cells, the use of liquid fertilizer; stage 2 technical training covering the use of solar cells; stage 3 managerial training in the form of financial management and digital marketing; and stage 4 practical demonstrations on the KWT land. The results of the activities showed an increase in knowledge and skills, including (1) training in financial administration and digital marketing increased the average knowledge of participants from 61.5 to 84.8 with a significant change of 23.3 points; (2) training in making organic liquid fertilizer succeeded in providing practical skills to 30 participants in processing household waste into environmentally friendly fertilizer; (3) training on the use of solar panels increased participants' knowledge from 90.5 to 96.4, a change of 5.8 points; (4) participants' responses to the training method showed that 75 percent agreed; and (5) a survey on understanding solar cell maintenance showed that 81 percent of participants agreed. Thus, this community service activity effectively increased knowledge of production, management, and the use of renewable energy technology to support hydroponic farming.